Purun Puppet Theatre: Weaving Stories on an Ecopedagogical Stage for the Sustainability of Cultural and Environmental Wisdom - Nawung Asmoro Girindraswari; Marissa Aulia Mayangsari (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2026)
Ecological crises, marked by environmental degradation and the weakening of human–nature relationships, reflect the limitations of environmental education paradigms that remain dominated by cognitive and normative approaches. Such approaches often fail to cultivate ecological awareness grounded in lived experience, cultural contexts, and community-based social practices. This study aims to analyze Purun Puppet Theatre as an arts-based ecopedagogy model that supports the sustainability of environmentally grounded cultural wisdom. The study employed Participatory Action Research and Arts-Based Research, involving 31 participants in Palangka Raya. PAR was used to examine the production process of Purun Paper Puppets, while ABR was applied to analyze the implementation of Purun Puppet Theatre as an ecopedagogical stage. Post-performance sustainability implications were explored through Focus Group Discussions (FGDs), and all data were interpreted within the conceptual frameworks of PAR and ABR. The findings indicate that Purun Puppet Theatre operates through three epistemic stages. First, formation of praxis, referring to the development of ecological understanding through the production of Purun Paper Puppets, integrating purun materiality, place-based experiences, and community participation as ecological learning practices. Second, knowledge production, referring to the implementation of Purun Puppet Theatre as an ecopedagogical stage that generates cultural–ecological knowledge through relationships among puppets, materials, narratives, audiences, and the social space of performance. Third, knowledge translation, referring to the translation of environmentally grounded cultural wisdom through post-performance reflection, strengthening ecological awareness, empathy toward human–nature relationships, and the reinterpretation of local purun wisdom within the context of environmental sustainability. This study demonstrates that Purun Puppet Theatre functions not only as a medium for communicating ecological messages but also as an arts-based ecopedagogy model that produces and translates cultural–ecological knowledge in reflective, participatory, and contextual ways.